Promotion of African indigenous business models through film: An exploration of Igbo trade apprenticeship through Netflix 2024 Afamefuna - An Nwa-Boi Story. - Nwoga Chibuzor Cosmas; Nwankiti Chukwuemeka Ononuju; Chime-Nganya Chioma Rose; Ogbin Ogban Obin; Ngwu Ogonnaya Lynda; Nwakpu Sanita Ekwutosi (Lakhomi Journal Scientific Journal of Culture, 2024)
This study explores the Igbo trade apprenticeship system as an indigenous business model, using a Netflix film, Afamefuna - An Nwa-Boi Story (2024) as a primary source. The thrust is to examine how film communicates ideology by discussing the tenets of the trade apprenticeship system among the south-east people of Nigeria called Ndigbo. Methodologically, it makes use of focus group discussions, in-depth interview and textual analysis to investigate the objectives of the study. The findings indicate film as a veritable tool in creating awareness and promoting the trade apprenticeship model as a panacea to unemployment, especially among the young people of Nigeria, most of who suffer in idleness after graduation from school because there is no job provided by the government for them. Thus, while it is recommended that the Nigerian government encourages the apprenticeship model by replicating it across her numerous agencies as a way of training young people in skills, the main thesis of this paper is that Nollywood filmmakers ought to start doing more of service-oriented movies that beyond entertainment values can point to answers that viewers look out for in life as is the case with Afamefuna that highlights the nwa-boi model for business minded people.